Development of Systemic Inflammatory Reaction after Aortocoronary Bypass Surgery: New Aspects - V. V. Moroz; A. B. Salmina; A. A. Fursov; S. V. Mikhutkina; K. A. Linev; S. V. Shakhmayeva (Общая реаниматология, 2008)
Objective: to optimize the diagnosis of a systemic inflammatory reaction (SIR) after aortocoronary bypass surgery (ACBS) under extracorporeal circulation (EC), by examining the reaction of the peripheral blood lymphocytic plasma membrane to surgery. Subjects and methods. Eighty-three patients with coronary heart disease (CHD) who had undergone ACBS were examined. The lymphocytic plasma membrane was studied before and 1, 2, 3, and 7 days after surgery. Lymphocytes were derived on the ficoll-verografin (Pharmacia Chemical, Uppsala, Sweden) density gradient (p=1.077). The isolated cells were investigated by phase contrast microscopy (900X). Results. The patients with CHD were found to have perioperative peripheral lymphocytic plasma membrane changes (blebbing), the genesis of which was determined by impaired membrane-cytoskeleton interactions. More plasma membrane changes occurred throughout the postoperative period, with their maximum being recorded on day 1, which corresponded to the increase peak in the concentrations of interleukin-6 and tumor necrosis factor-а. Conclusion. The follow-up cell membrane changes appearing as peripheral lymphocytic blebbing reflect the development of SIR during ACBS under EC. In patients with CHD, the lymphocytic plasma membrane blebbing is of varying degrees: from early to terminal. The determination of peripheral lymphocytic blebbing allows one not only to record SIR, but also to assess its time course of changes. Key words: lymphocytic blebbing, systemic inflammatory reaction, aortocoronary bypass surgery, extracorporeal circulation.